1996
DOI: 10.1055/s-2008-1067981
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Induction and Ovarian Malignancy

Abstract: Many couples faced with infertility are treated with ovulation inducing medicines. Recently, concerns have been raised about the possible risk of ovarian malignancy after such ovarian stimulation. Theories of pathogenesis for ovarian cancer include incessant ovulation, elevated pituitary gonadotropins, genetic predisposition, and chemical carcinogens. Protective factors include suppression of ovulation, pregnancy, and castration. Low numbers of exposed women who develop ovarian cancer make this a difficult res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Some historical as well as more recent cohort studies showed an increased risk of ovarian cancer with the use of infertility treatment, such as CC and gonadotrophins . This led some reviewers to conclude that the risk of ovarian cancer, if such a risk exists, is two to three times higher than the risk for the general population, with the lifetime risk of ovarian cancer in the general population quoted at 1 in 70 (~1.43%); thus, an equivalent risk for patients treated with fertility drugs may carry a 4–5% lifetime risk …”
Section: Fertility Treatment and Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Some historical as well as more recent cohort studies showed an increased risk of ovarian cancer with the use of infertility treatment, such as CC and gonadotrophins . This led some reviewers to conclude that the risk of ovarian cancer, if such a risk exists, is two to three times higher than the risk for the general population, with the lifetime risk of ovarian cancer in the general population quoted at 1 in 70 (~1.43%); thus, an equivalent risk for patients treated with fertility drugs may carry a 4–5% lifetime risk …”
Section: Fertility Treatment and Ovarian Cancermentioning
confidence: 99%
“…16 This led some reviewers to conclude that the risk of ovarian cancer, if such a risk exists, is two to three times higher than the risk for the general population, with the lifetime risk of ovarian cancer in the general population quoted at 1 in 70 (~1.43%) 17 ; thus, an equivalent risk for patients treated with fertility drugs may carry a 4-5% lifetime risk. 18 The paper by Rossing et al 15 in 1994 led to significant change in practice regarding the use of CC, as it concluded that the latter increased the risk of borderline and invasive ovarian cancer. This was even more so when CC was taken for 12 or more cycles with a relative risk (RR) of 2.3 in general and 11.1 (with 12 or more cycles) compared with infertile women with no CC use (95% CI 0.5-11.4 and 1.5-82.3 respectively).…”
Section: Ethical Issues Introductionmentioning
confidence: 99%
“…Accordingly, the risk for women for the development of ovarial cancer under an increased ovarian activity caused by ovulation stimulating pharmaceutical therapy rises about 100% compared with the risk of women without such a medication. (181,4,19,67) Following conclusion can be derived from that: The commitment of pharmaceuticals in the therapy of infertility, which increases the number of ovulations can lead directly to an increased risk for ovarial cancer. The hazard for the development of a malignant tumor with a low malignant potential lies at 143% (18).…”
Section: Womens' Risksmentioning
confidence: 99%
“…These reports are published in all sides known journals as for example Human Reproduction. Facts on ART are presented to the public in almost every European country; however, they are hardly mentioned in Croatia (1,2,3,4,5,6,7,8,9,10,11,12,14,15,16,17,18,19,20,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses about the etiology of ovarian cancer have been proposed. “Gonadotropin hypothesis” states that increased exposure to the gonadotropins, follicle stimulating hormone (FSH) and lutenizing hormone (LH), leads to ovarian surface epithelium (OSE) transformation [20] which is supported by evidence that as women enter menopause, their levels of FSH and LH are very high, which corresponds with the age that most women develop ovarian cancer [21]. “Tubal hypothesis” has emerged which proposes that ovarian cancer may not originate from the ovary at all, but rather arises from the oviduct [22,23] in a way that Fallopian tube exposure to the same microenvironment as the ovary which contains many inflammatory factors may potentially damage OSE and induce mutation and transformation.…”
Section: Introductionmentioning
confidence: 99%